On the nature of verb–noun dissociations in bilectal SLI: a psycholinguistic perspective from Greek - Kambanaros, Maria; Grohmann, Kleanthes K.; Theodorou, Elena (My University, 2014)
We report on object and action picture-naming accuracy in two groups of bilectal speakers in Cyprus, children with typical language development (TLD) and children with specific language impairment (SLI). Object names were overall better retrieved than action names by both groups. Given that comprehension for action names was relatively intact for all children, this finding is taken to be the result of a breakdown at the interface of the semantic lexicon and phonological representations, or access to them. The results complement similar research on English, a minimally inflected language in contrast to Greek. Overall, cross-linguistic word class effects provide strong evidence for the hypothesis that grammatical category is an organizing principle shared across languages. Finally, our results suggest that bilectal children with SLI present with general lexical delay rather than a deficit in verb naming per se.
Keywords: Object and action naming; Specific language impairment; Bilectal children; Lexical delay